Identification of morphological descriptors for characterization of cassava (Manihot esculenta Crantz) in Vietnam based on km 94 variety - Ha, Chu Duc; Ngoc Quynh, Le Thi; Hien, Nguyen Trong; Ham, Le Huy; Dung, Le Tien (Academia Journal of Biology, 2015)
Morphological descriptors are indispensable tools for management, maintenance and utilization of plant genetics resources for cassava seed systems all over the world. In Vietnam, only a few of taxonomic studies on cassava varieties based on morphological descriptors. This study was proposed to select descriptors for the characterization of cassava (Manihot esculenta Crantz) cv. KM 94 (Kasetsart 50/KU50) which is widely cultivated in Vietnam. Twenty descriptors were selected from Standard Characterization System of the International Union for the Protection of New Varieties of Plants (UPOV) and the International Institute of Tropical Agriculture (IITA). These characteristics whose expression is little influenced by the environment, are relatively easy to measure in the field. Scoring scales were based on the popularity of each characteristic. It is proposed that measurements are taken according to 20 descriptors: 2 descriptors of apical leaves, 4 descriptors of mature leaves, 2 descriptors of petioles, 7 descriptors of stems and 5 descriptors of roots. To analyze data together and draw comparisons, it is useful for KU50’s full charaterization being the same with KM 94 which is collected in Vietnam. Twenty descriptors will be further analyzed to characterize cassava varieties in Vietnam.